International Norms on Cross-Border Data Protection in the Era of Global Cyber Threats - Maulana Fahmi Idris (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The rising volume of international data transfers in the modern digital era has created new cybersecurity threats that require improved legal frameworks for data protection. This study evaluates international norms by examining how global cyber threats operate in the present world. The research uses a normative juridical framework to analyze 32 international legal instruments and 45 scholarly articles published between 2018 and 2025 through both normative and comparative analytical methods. The study demonstrates that current regulatory systems are divided into separate parts, which are mostly controlled by non-binding rules that do not have standardized methods for enforcement and thus depend on each country's ability to enforce them, while international enforcement remains inadequate. The situation develops into a more severe problem because cyber threats now develop more advanced systems than existing rules can match. The research demonstrates the critical need for countries to establish uniform regulations while developing stronger compliance methods and building faster international partnership systems. The research presents a framework that connects international law and cybersecurity through a more extensive analytical approach.